ANTIFUNGAL ACTIVITY OF PLANT EXTRACTS ON COLLETOTRICHUM GLOEOSPORIOIDES INFECTING JATROPHA CURCAS - R. HEGDE, YASHODA; TIPPESHI L. CHAVHAN; RAJALAXMI S. KESHGOND (The Bioscan, 2014)
Nine different plant extracts were evaluated against Colletotrichum gloeosporioides, viz. Glyricidia, neem, onion, eucalyptus, duranta, ocimum, garlic, ginger at two concentrations (5 and 10 per cent) and Azadirachtin (2.5 and 5.0 per cent). Azadirachtin was found to be the best in mycelial growth inhibition (89.25%) followed by ginger (48.05%) and onion (38.05%) whereas Azadirachtin and garlic bulb extract were best in complete inhibition of sporulation of C. gloeosporioides.